Landasan Filosofis Hukum Ekonomi Syari'ah dan Relevansinya dalam Pengembangan Strategi Marketing - Hidayat, Asep Dadang; Mulyadi, Mulyadi; Nurachmad, Senki; Abdillah, Yudi Khoeri; Hasan, Jawahiroh Musfiyah Al (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Abstract: This research aims to investigate the legal and philosophical foundations of Syari’ah economics and its relevance in the development of marketing strategies. Syari’ah economics has unique philosophical underpinnings, involving Islamic principles, ethics, and social justice. In the business context, applying Syari’ah economic law brings financial benefits and positively impacts the company's image and customer trust. This research is a qualitative approach that uses literature analysis and descriptive studies, relevant data are collected through a comprehensive literature study, then identified and analyzed with a thematic analysis approach. The results of this study provide a better understanding of how the principles of shari'ah economic law can be applied in the development of a successful marketing strategy. It is hoped that this journal can provide insights to business practitioners, researchers, and policymakers on the potential of the Syariah economy and how to apply it to achieve success in marketing.